1999
DOI: 10.1016/s0014-5793(99)01178-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of an alkaloid pheromone from the pale‐brown chafer, Phyllopertha diversa (Coleoptera: Scarabaeidae), by an insect olfactory cytochrome P450

Abstract: The pale-brown chafer, Phyllopertha diversa, utilizes an unusual alkaloid, 1,3-dimethyl-2,4-(1H,3H)-quinazolinedione, as its sex pheromone. This compound is rapidly degraded in vitro by the antennal protein extracts from this scarab beetle. Demethylation at the N-1 position and hydroxylation of the aromatic ring have been identified as the major catabolic pathways. The enzyme responsible for the pheromone degradation is membrane-bound, requires NAD(P)H for activity and is sensitive to cytochrome P450 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…PdivPDE is specific to antennae (see above). Pheromone degradation by antennal enzyme(s) is inhibited by metyrapone (12). Electrophysiological studies (2,3,(21)(22)(23)(24)(25) led to mapping the pheromone-detecting sensilla placodea and those tuned to other semiochemicals in P. diversa and other scarab beetle species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PdivPDE is specific to antennae (see above). Pheromone degradation by antennal enzyme(s) is inhibited by metyrapone (12). Electrophysiological studies (2,3,(21)(22)(23)(24)(25) led to mapping the pheromone-detecting sensilla placodea and those tuned to other semiochemicals in P. diversa and other scarab beetle species.…”
Section: Resultsmentioning
confidence: 99%
“…1. Structures of P. diversa sex pheromone DMQ (1) and metyrapone, a compound that inhibits pheromone degradation by a male antennae-specific cytochrome P450 (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the degradation along with potential cofactors or inhibitors showed that the enzymatic system requires NADPH and NADH for activity. On the other hand, the enzymatic activity was inhibited by proadifen and metyrapone, two general widely used inhibitors for cytochrome P450 [11].…”
Section: Pheromone-degrading Enzymesmentioning
confidence: 99%